PERAN MODERASI LITERASI KEUANGAN SYARIAH PADA THEORY PLANNED BEHAVIOUR (TPB) TERHADAP KEPUTUSAN MENABUNG DI BANK SYARIAH: STUDI PADA PEMILIK UMKM DI KABUPATEN BONE - Ihzani, Masdathul; Marzuki, Sitti Nikmah; Ida Farida (Journal of Islamic Economics and Finance, 2025)
This research aims to analyze the role of Islamic financial literacy as a moderating variable in the Theory Planned Behavior (TPB) model on savings decisions in Islamic banks. This research uses a quantitative approach with a survey method involving 100 respondents who own UMKM in Bone Regency. The variables analyzed include attitudes, subjective norms, and perceived behavioral control as predictors of saving decisions, with Islamic financial literacy as a moderating variable. Data was collected through questionnaires and analyzed using the SmartPLS application for testing regression models using the Moderated Regression Analysis (MRA) approach. The research findings show that although subjective norms do not influence the decision to save at a Sharia bank, attitudes and perceived behavioral control do. Perceived behavioral control can moderate the decision to save at a Sharia bank, but Sharia financial literacy cannot moderate attitudes and subjective norms around this choice. This research provides important implications for the development of sharia financial literacy among UMKM as an effort to increase their participation in sharia banking. In addition, it is hoped that the results of this research can become a reference for Islamic banks and regulators in designing relevant financial education and product innovation strategies.